Impact of low-carbon economic policies on the corporate environmental responsibility model in China. - Hongya Liu; Haslindar Lbrahim; Meijing Song (PLoS ONE)
This study investigates the impact of low-carbon economic policies on Corporate Environmental Responsibility (CER) in Chinese A-share listed companies, with a particular focus on the role of financing constraints as a mediating factor. Despite a decrease in environmental pollution incidents in 2022, the economic and social impacts of such incidents remain significant, highlighting the need for stronger environmental governance. Building upon previous research, this study utilizes data from the Shanghai and Shenzhen stock exchanges (2010-2020) and employs a Difference-in-Differences (DID) model to assess the effects of low-carbon economic policies introduced in 2016 on CER. The findings reveal that these policies positively influence CER and that financial constraints act as a mediator. The study finds how low-carbon policies indirectly promote environmental commitments by alleviating financial barriers. The research provides valuable insights for policy formulation, advocating for intensified reforms on the financial supply side to foster a sustainable economic framework. Additionally, it underscores the importance of implementing robust low-carbon policies to elevate corporate environmental responsibility. However, the study also notes limitations related to data scope and potential external factors influencing the results. These findings contribute to the broader discourse on sustainable development, offering a blueprint for harmonizing economic growth with environmental preservation and informing future research in this area.